Recurrent vulvar carcinoma - reconstruction options with review of literature - Jeevarajan, Sakthi Usha Devi; Srinivas, Karnan; Harikrishnan, Prasanna Srinivasa Rao; Balamurugan, T. D.; Prabu, M. J. (International Journal of Research in Medical Sciences, 2025)
Vulvar cancer is a rare gynecological malignancy that can be aggressive and have a high rate of recurrence. The surgical management of recurrent vulvar cancer often involves wide local excision and the use of various reconstructive techniques to restore formal function. The keystone flap is a type of local tissue flap that has gained popularity in recent years due to its versatility and low complication rates. Our patients are elderly female who had previously undergone modified radical vulvectomy with bilateral inguinal femoral lymph nodal dissection for vulvar cancer. They presented symptoms and signs of recurrence and underwent wide local excision along with a keystone flap reconstruction. The postoperative course was uneventful, and the patient had no complications. Lotus petal suprafascial flap is a simple alternative procedure that can be done during the same surgery as the radical vulvectomy, improving the aesthetic results and reducing both the rate of complications and hospital stay. Soft tissue reconstruction in patients undergoing resection of recurrent vulvar malignancies is associated with a low rate of postoperative complications, decreased pain, and improved functional status.